Familial love discourses in contemporary German-language drama and theater - Petrović-Ziemer, Ljubinka (Primerjalna književnost, 2016)
This analysis of familial love discourses in contemporary German-language drama and theater, prefaced by a brief overview mainly of the development of the bourgeois family formation and family-related discourses in German-language drama and theater tradition since the eighteenth century, examines which theatrical and dramatic tradition playwrights resort to in their work and how they modify it under postdramatic conditions. This contribution is also guided by the question of whether contemporary plays, which grotesquely overdraw familial interrelations, treat the subject of love as a phantasm and whether the gloomy family plays written and staged since the 1990s also offer alternative visions of viable and caring love.
Keywords: Loher, Dea, 1964-; Specht, Kerstin, 1956-; Bärfuss, Lukas, 1971-; Mayenburg, Marius von, 1972-; Jonigk, Thomas, 1966-; nemška dramatika; theater; gledališče; družinska drama; družinski odnosi; ljubezen; love